2022
DOI: 10.1029/2021jc018179
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biogeochemical Influences on Nutrients Through the Canadian Arctic Archipelago: Insights From Nitrate Isotope Ratios

Abstract: The Canadian Arctic Archipelago (CAA) provides a gateway for the flow of nutrients from the North Pacific to the North Atlantic. The transport and biogeochemical cycling of nutrients throughout the CAA, however, are sparsely documented. Here, we report water column nitrogen and oxygen isotope ratios of nitrate (δ15NNO3 and δ18ONO3) collected in a throughflow of the CAA into Baffin Bay, providing insights on inherent nutrient dynamics. The nitracline shoaled eastward into the CAA, wherein large subsurface chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 111 publications
(228 reference statements)
0
11
0
Order By: Relevance
“…However, due to its slow oxidation kinetics and potential photoinhibition of MnOB in the shallow Chukchi shelves (< 50 m), most of the Mn in the winter Bering Sea Water remains in the dissolved phase during across‐shelf transport, leaving Chukchi shelf waters virtually depleted of Mn oxides and highly enriched in dissolved Mn (Jensen et al 2020; Xiang and Lam 2020). In the shallow Canadian Arctic Archipelago shelves, the lower pulses of organic matter, compared with the Chukchi Shelf, and the strong mixing regimes do not favor reductive benthic conditions, and thus, sedimentary supply of reduced Mn(II) is not anticipated to be significant (Colombo et al 2021; Lehmann et al 2022). Therefore, the excess of particulate Mn over continental crust values across the Canadian Arctic Ocean, and especially in halocline waters, is most likely explained by the authigenic formation of Mn(III/IV) oxides in the water column.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to its slow oxidation kinetics and potential photoinhibition of MnOB in the shallow Chukchi shelves (< 50 m), most of the Mn in the winter Bering Sea Water remains in the dissolved phase during across‐shelf transport, leaving Chukchi shelf waters virtually depleted of Mn oxides and highly enriched in dissolved Mn (Jensen et al 2020; Xiang and Lam 2020). In the shallow Canadian Arctic Archipelago shelves, the lower pulses of organic matter, compared with the Chukchi Shelf, and the strong mixing regimes do not favor reductive benthic conditions, and thus, sedimentary supply of reduced Mn(II) is not anticipated to be significant (Colombo et al 2021; Lehmann et al 2022). Therefore, the excess of particulate Mn over continental crust values across the Canadian Arctic Ocean, and especially in halocline waters, is most likely explained by the authigenic formation of Mn(III/IV) oxides in the water column.…”
Section: Resultsmentioning
confidence: 99%
“…Dissolved Mn increases near the ocean floor in the Canadian Arctic by sediment resuspension (non‐reductive dissolution; Colombo et al., 2020). While reductive dissolution is important over the Chukchi Shelf regions (Vieira et al., 2019), we did not include sediment diffusion as reducing conditions in the sediments are not prevalent in the CAA (Colombo et al., 2021; Lehmann et al., 2022). The northern and western model boundary conditions from the global Mn model (Van Hulten et al., 2017) may account for some inflow of reduced Mn from the Chukchi shelves, as the global model includes sediment diffusion.…”
Section: Methodsmentioning
confidence: 99%
“…This current upwells in the eastern sector of the NOW to the base of the turbulent surface layer, and a flow component also veers west to feed into the south‐flowing Baffin Island Current (Dumont et al, 2010; Melling et al, 2001). Colder and fresher (<−0.4°C; <33.5 psu; Münchow et al, 2015) silicate‐ and phosphate‐rich (up to 18 and 1.1 μmol kg −1 , respectively; Burgers et al, 2023) Pacific‐derived Arctic waters have been reported to enter the NOW from the north through Nares Strait (sill depth of 220 m; Lehmann et al, 2022; Tremblay et al, 2002) driven by strong and persistent northerly winds and a sea‐level difference between the Lincoln Sea and northern Baffin Bay. However, it is worth noting that the water mass assembly and nutrient content entering Nares Strait from the Lincoln Sea vary under different atmospheric forcing patterns (i.e., Arctic Oscillation modes), with increased contribution of the fresher and nutrient‐depleted (nitrate concentrations below 1 μM during winter; Brown et al, 2020) surface waters of the Canada basin during positive phases of the Arctic Oscillation and increased contribution of the comparatively nutrient‐rich waters (nitrate concentrations up to 3.5 μmol kg −1 ) of the Siberian shelves during neutral/negative phases of the Arctic Oscillation (Burgers et al, 2023).…”
Section: Ocean Circulation and Sea‐ice Conditionsmentioning
confidence: 99%